2014
DOI: 10.1097/aog.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Estrogen for Genitourinary Syndrome of Menopause

Abstract: OBJECTIVE To comprehensively review and critically assess the literature on vaginal estrogen and its alternatives for women with genitourinary syndrome of menopause and to provide clinical practice guidelines. DATA SOURCES MEDLINE and Cochrane databases were searched from inception to April 2013. We included randomized controlled trials and prospective comparative studies. Interventions and comparators included all commercially available vaginal estrogen products. Placebo, no treatment, systemic estrogen (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(159 citation statements)
references
References 66 publications
5
150
0
4
Order By: Relevance
“…Importantly, these improvements occurred without significantly elevating their serum estradiol levels when sampled with a highly-sensitive radioimmunoassay. This information is consistent with the published literature and can be used when counseling older women with vaginal atrophy who may be concerned about initiating intravaginal estrogen therapy [1, 15–18]. …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Importantly, these improvements occurred without significantly elevating their serum estradiol levels when sampled with a highly-sensitive radioimmunoassay. This information is consistent with the published literature and can be used when counseling older women with vaginal atrophy who may be concerned about initiating intravaginal estrogen therapy [1, 15–18]. …”
Section: Discussionsupporting
confidence: 84%
“…Low dose vaginal estrogen is an effective treatment for atrophy symptoms [1718]. This study showed that older women using 50mcg of intravaginal estradiol nightly for 8 weeks followed by twice weekly for 8 weeks had improvements in their VMI and vaginal symptoms of dryness and itching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have noted that tablets, the ring, and creams have comparable efficacy in treating vulvovaginal symptoms. 74 Vaginal estrogen has also been found to reduce risk of recurrent UTIs and overactive bladder symptoms in menopausal women. The low-dose vaginal estradiol ring is approved to treat urinary urgency and dysuria.…”
Section: Hormonal Prescription Medicationsmentioning
confidence: 99%
“…Postmenopausal women are characterised by reduced oestrogen levels and those suffering rUTIs typically show a vaginal pH above 4.5,12 suggesting that the reduced oestrogen levels impact negatively on Lactobacilli growth, which adversely affects the vaginal microbiome 13, 14, 15. In support of a role for oestrogen in the innate defence of the urogenital tract, topical, but not oral oestrogen treatments have proven successful in reducing infections with these effects mediated through the vaginal commensal populations and the urogenital innate defences 16, 17, 18, 19. However, because of the side effects, the use of topical vaginal oestrogen is not always appropriate for all women20 and hence its therapeutic potential in treating rUTIs is limited.…”
Section: Introductionmentioning
confidence: 99%